Estimating Reliability of Telecommunication and Electronic Devices - Aamir, Muhammad (My University, 2015)
This talk mainly focused on understanding of reliability parameters such as Mean Time Between Failures (MTBF) and Mean Time To Repair (MTTR). These parameters are further explored for estimation of reliability with special reference to Telecommunication and electronic devices. This talk is being augmented by adding few practical analyses of interest. Moreover, the topic is also linked with electronic design automation considering concept of Built In Self Test (BIST) for electronic chips and circuits based systems containing Telecommunication and electronic devices.
Keywords: Electrónica Aparatos e instrumentos; Reliability